2017
DOI: 10.1016/j.jmateco.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Discrete-space agglomeration model with social interactions: Multiplicity, stability, and continuous limit of equilibria

Abstract: This study examines the properties of equilibrium, including the stability, of discretespace agglomeration models with social interactions. The findings reveal that while the corresponding continuous-space model has a unique equilibrium, the equilibrium in discrete space can be non-unique for any finite degree of discretization by characterizing the discrete-space model as a potential game. Furthermore, it indicates that despite the above result, any sequence of discrete-space models' equilibria converges to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Bragard and Mossay (2016) studied a relocation dynamics in the continuous-space framework of Mossay and Picard (2011). Akamatsu et al (2017) formulated a discrete-space version of Beckmann (1976)'s model as a potential game and elucidated its properties. Unification of this line of researches can lead to a fruitful field of applications of the potential game method.…”
Section: Related Literaturementioning
confidence: 99%
“…Bragard and Mossay (2016) studied a relocation dynamics in the continuous-space framework of Mossay and Picard (2011). Akamatsu et al (2017) formulated a discrete-space version of Beckmann (1976)'s model as a potential game and elucidated its properties. Unification of this line of researches can lead to a fruitful field of applications of the potential game method.…”
Section: Related Literaturementioning
confidence: 99%
“…See, for instance, previous studies by (Akamatsu et al, 2012;Ikeda et al, 2012;Osawa et al, 2017;Ikeda et al, 2018).…”
Section: Evolution Of Spatial Structurementioning
confidence: 85%
“…Remark 5.1. The empirical evidence on regional agglomeration presented by Duranton and This is the "spatial period-doubling cascade" behavior discussed by (Akamatsu et al, 2012;Osawa et al, 2017;Ikeda et al, 2018). Next, Figure 11 shows the results for a Class II model, namely, the Allen and Arkolakis (2014).…”
Section: Evolution Of Spatial Structurementioning
confidence: 89%
See 1 more Smart Citation
“…Stability characterization in such continuous-space models is difficult, although some authors have tackled this problem (for example, Bragard and Mossay, 2016). Instead, by considering discrete-space versions of Beckmanntype models, Akamatsu et al (2017) provided a potential function that can be used to characterize the stability of equilibria through more elementary means of finite-strategy evolutionary dynamics (as surveyed by Sandholm, 2010). Similarly, Osawa and Akamatsu (2020) showed that Fujita and Ogawa (1982)'s seminal urban economics model on the formation of multiple business districts in a city is an instance of potential games when formulated in discrete space; global maximization of the potential function is also an effective method of analysis in this model.…”
Section: Introductionmentioning
confidence: 99%